Design Dan Implementasi Sistem Informasi Akuntansi Untuk Efisiensi Pengelolaan Keuangan Pada Ekowisata Bale Mangrove Jerowaru - Feni Aswiwanti; Yusli Mariadi (Jurnal Riset Mahasiswa Akuntansi, 2026)
Financial management at Bale Mangrove Jerowaru Ecotourism is still conducted manually, making the process relatively complicated and time-consuming. This study aims to design and implement a web-based Accounting Information System (AIS) to improve the efficiency of financial management. The research employs a qualitative approach using the prototyping method, which includes user needs identification, interface design, prototype development, system testing, and refinement. The results indicate that the implementation of the web-based AIS at Bale Mangrove Jerowaru Ecotourism enhances time and labor efficiency, improves ease and accuracy in financial management, and strengthens organizational governance through better control mechanisms and transparency. Therefore, the developed system facilitates transaction recording, accounting data processing, and the preparation of periodic financial reports.